STATE OF THE SPECIALIZED RHEUMATOLOGIC ASSISTANCE FOR THE CHILDREN AND ADULTS IN THE RUSSIAN FEDERATION. THE PROJECT OF THE FEDERAL PURPOSE ORIENTED PROGRAM «RHEUMATIC DISEASES IN 2008–2012» (BASED ON THE REPORT DELIVERED AT THE PRESIDIUM SESSION OF THE R - A.A. Baranov; E.L. Nasonov; E.I. Alexeeva; S.F. Erdes; A.G. Il'yin (Вопросы современной педиатрии)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2007;6(1):6-8)